2016
DOI: 10.18632/aging.101076
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Salvia haenkei as gerosuppressant agent by using an integrated senescence-screening assay

Abstract: Cellular senescence is a stable cell cycle arrest that is the causative process of aging. The PI3K/AKT/mTOR pathway is implicated in the control of cellular senescence and inhibitors of this pathway have been successfully used for life span prolongation experiments in mammals. PTEN is the major regulator of the PI3K/AKT/mTOR pathway and loss of PTEN promotes a senescence response termed PICS. Here we report a novel-screening assay, for the identification of compounds that block different types of senescence re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 48 publications
2
12
0
Order By: Relevance
“…In this work we analyse data from the DrugAge database [ 10 ], which contains information about chemical compounds and their effect on the lifespan of organisms. DrugAge contains a variety of compounds with anti-ageing properties such as gerosuppressant, geroprotective and senolytic activity [ 11 13 ] as well lifespan increasing properties for a specific species. Existing databases with lifespan-extending drugs include AgeFactDB ( http://agefactdb.jenage.de/ ) [ 14 ], and Geroprotectors.org [ 15 ] ( http://geroprotectors.org/ ).…”
Section: Introductionmentioning
confidence: 99%
“…In this work we analyse data from the DrugAge database [ 10 ], which contains information about chemical compounds and their effect on the lifespan of organisms. DrugAge contains a variety of compounds with anti-ageing properties such as gerosuppressant, geroprotective and senolytic activity [ 11 13 ] as well lifespan increasing properties for a specific species. Existing databases with lifespan-extending drugs include AgeFactDB ( http://agefactdb.jenage.de/ ) [ 14 ], and Geroprotectors.org [ 15 ] ( http://geroprotectors.org/ ).…”
Section: Introductionmentioning
confidence: 99%
“…Cellular senescence is defined as a stable arrest of cell growth that occurs in all human cells during aging [ 15 17 ]. As a result of stressful events, such as oncogene over-expression, ROS generation and DNA damage (for example induced by UVR, in particular by UVB light), cells may prematurely become senescent [ 18 ]. In this scenario, it appears evident the importance of developing innovative strategies able to prevent the accumulation of senescent cells or to selectively kill them, thus counteracting aging and aging-associated disorders.…”
Section: Introductionmentioning
confidence: 99%
“…In this scenario, it appears evident the importance of developing innovative strategies able to prevent the accumulation of senescent cells or to selectively kill them, thus counteracting aging and aging-associated disorders. Recently, we identified Salvia haenkei (SH), a Bolivian plant rich in vitamin B and antioxidant properties, as a potential anti-senescence agent [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a new medical use was attributed to Salvia haenkei , thanks to the research of Alimonti et al, that demonstrated an antisenescence activity of Salvia haenkei , suggesting a potential use of Salvia haenkei based products for antiaging skin treatments. 9 , 10 …”
Section: Introductionmentioning
confidence: 99%